A clinical analysis of clinicopathological features and prognostic factors of triple-negative breast cancer - Oana-Adriana Rajput-Anghel; Traean Burcos (Romanian Journal of Medical Practice, 2024)
Objectives. The aim of this study was to explore the clinicopathological characteristics, prognostic factors, recurrence patterns and survival analysis of triple negative breast cancer patients compared to non-triple negative breast cancer patients. Materials and methods. The cohort included 420 patients who were diagnosed with breast cancer. The patients were evaluated based on the molecular classification and grouped into TNBC and non-TNBC. Data was explored using SPSS Version 29.0.0.0. Patient and tumor characteristics were studied. Univariate and multivariate Cox Regression was used to analyze prognostic factors. Kaplan Meier method with the logrank test was performed to observe DFS and OS. Outcomes. The triple negative subtype was observed in 57(13.6%) patients. Patients with TNBC had a greater proportion of grade 3 tumors compared to those with non-TNBC (43.9% vs. 5.5%, p<.001). In the univariate analysis pathological type, tumor size, tumor grade, nodal invasion, lymphovascular invasion, perineural invasion and extra-nodal extension were identified as statistically significant prognostic factors. The mean time to relapse for TNBC was lower 60.0 (95% CI, 37.16 to 82.83) compared to the non-TNBC group with a mean time to relapse of 72.0 months (95% CI, 55.81 to 88.18), nevertheless distributions were not statistically significant X2 (1)=1.524, p.217. Mean overall survival was 80.53 months (95% CI, 77.75 to 83.32) in non-TNBC compared to TNBC of 80.04 month (95% CI, 66.76 to 93.33) with a non-statistically significantly Log rank test X2 (1)=1.252, p.263. Conclusions. Triple negative breast cancer represents a heterogenous molecular and prognostic group of tumors which needs further clinical trials in order to develop targeted therapies.